CURAHAN WAKTU KERJA DAN PENGAMBILAN KEPUTUSAN WANITA DALAM KELUARGA PETANI KELAPA SAWIT POLA SWADAYA DI DESA PANTAI CERMIN KECAMATAN TAPUNG KABUPATEN KAMPAR - Yusmaniar '; Rosnita '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to: 1) Analysis the amount of working hours of women in the household and productive businesses of family palm oil innate pattern farmers 2) Knowing the dominant factors that affect the working hours of women in household palm oil innate pattern farmers; 3) Knowing the pattern of decision-making of women in family palm oil innate pattern farmers. The research used a survey method and sampling as many as 32 ​​samples. Analysis of the data using Ordinary Liest Square (OLS) and The Likert Scale's Summated Ratting (SLR). The results showed that the average working hours of productive women in the village of Pantai Cermin is high at 36,46 HKP/week when compared to average of productive working hours of women are only 20,39 HKP/week. The dominant factors that affect working hours is factor revenue wife. The pattern of household decision-making is dominated by a woman or a farmer's wife. Key words : Working time, decision making, innate pattern farmers